2006
DOI: 10.1038/sj.emboj.7601403
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase II bypass of oxidative DNA damage is regulated by transcription elongation factors

Abstract: Oxidative lesions represent the most abundant DNA lesions within the cell. In the present study, we investigated the impact of the oxidative lesions 8-oxoguanine, thymine glycol and 5-hydroxyuracil on RNA polymerase II (RNA pol II) transcription using a well-defined in vitro transcription system. We found that in a purified, reconstituted transcription system, these lesions block elongation by RNA pol II to different extents, depending on the type of lesion. Suggesting the presence of a bypass activity, the bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
138
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(154 citation statements)
references
References 58 publications
(57 reference statements)
12
138
1
1
Order By: Relevance
“…Thus, it seems that RNAP preferentially incorporates the correct C opposite the 8OG, effectively limiting the mutagenic potential of this lesion with respect to transcription. Previous reports using cell-free systems have indicated that Ϸ8% of transcripts generated by elongation past 8OG are mutant (31), with the majority containing a C opposite the template lesion (12), in agreement with the data presented here. Interestingly, sequence analysis of truncated transcripts arising from RNAP pausing at the site of damage also indicates that the insertion of A occurs only approximately 8% of the time (32), suggesting that these transcripts are likely to be eventually elongated to full-length, in agreement with data provided by single initiation transcription reactions (29).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, it seems that RNAP preferentially incorporates the correct C opposite the 8OG, effectively limiting the mutagenic potential of this lesion with respect to transcription. Previous reports using cell-free systems have indicated that Ϸ8% of transcripts generated by elongation past 8OG are mutant (31), with the majority containing a C opposite the template lesion (12), in agreement with the data presented here. Interestingly, sequence analysis of truncated transcripts arising from RNAP pausing at the site of damage also indicates that the insertion of A occurs only approximately 8% of the time (32), suggesting that these transcripts are likely to be eventually elongated to full-length, in agreement with data provided by single initiation transcription reactions (29).…”
Section: Discussionsupporting
confidence: 93%
“…It is difficult to imagine how 8OG might initiate TCR, because one requirement for this process is thought to be arrest of RNAP at the lesion site, and multiple laboratories using various systems have demonstrated that transcription past 8OG leads to a small population of truncated transcripts in the context of abundant full-length transcripts (11,12,28,29). The level of RNAP pausing can be influenced by various factors, including the sequence context and promoter strength (30), distance of the lesion from the transcription start site (30,31), the relative abundance of CTP and ATP in the reaction (12,29), and the presence of various elongation factors (31,32), but ultimately full-length transcripts are produced. Nevertheless, there is evidence for involvement of Csb in the global repair of 8OG, particularly when combined with the absence of Ogg1 (21, 22), and there is some suggestion that this role is independent of TCR (21).…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence that stalled RNAP II at bulky adducts activates the TC-NER pathway (36). However, the extent to which oxidized bases block transcription is unclear, with differing results depending not only on the nature of the lesion but also on the transcription system used (30,33,37,38) and possibly on the sequence context of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that the oxidative lesions 5-OHU, thymine glycol, and 8-oxoguanine all are bypassed during transcription in a reconstituted system, albeit to varying extents. When bypassed by RNAP II, the 5-OHU lesion is the most likely among these to produce a mutant transcript (33). We thus used 5-OHU-containing plasmid DNA in the repair assay.…”
Section: Neil2mentioning
confidence: 99%
“…Pode ocorrer também a formação de lesões em cluster, definidas pela presença de duas ou mais lesões (do tipo bases oxidadas, sítios AP ou quebras) dentro de uma ou duas voltas da hélice do DNA (Sage e Harrison, 2011 Charlet-Berguerand et al, 2006), enquanto polimerases ligadas a processos de reparo como a DNA polimerase beta (pol ) tendem a inserir a base correta, no caso C (Shibutani et al, 1991). Acredita-se que os efeitos deletérios dessa lesão estejam ligados principalmente à mutagênese, uma vez que por não ser uma lesão distorsiva, 8-OHdG causa uma parada apenas transiente da RNA polimerase II (Tornaletti et al, 2004;Kathe et al, 2004;Larsen et al, 2004); essa parada, entretanto, pode ser influenciada por outras variáveis como a concentração de ATP ou a sequência na qual a lesão está inserida (Allgayer et al, 2013).…”
Section: Estresse Oxidativo E Dano Ao Dnaunclassified